Expanding the medical physicist curricular and professional programme to include Artificial Intelligence. (March 2021) - Zanca, F.; Hernandez-Giron, I.; Avanzo, M.; Guidi, G.; Crijns, W.; Diaz, O.; Kagadis, G.C.; Rampado, O.; Lønne, P.I.; Ken, S.; Colgan, N.; Zaidi, H.; et al.
Highlights: We developed a Medical Physicists Curricular Program regarding AI. It can be considered as a supplement to all sub-speciality curricula of EFOMP. It is recommended to be utilised by national training and regulatory bodies. It can also be implemented via the European School of Medical Physics Expert modules. Abstract: Purpose: To provide a guideline curriculum related to Artificial Intelligence (AI), for the education and training of European Medical Physicists (MPs). Materials and methods: The proposed curriculum consists of two levels: Basic (introducing MPs to the pillars of knowledge, development and applications of AI, in the context of medical imaging and radiation therapy) and Advanced. Both are common to the subspecialties (diagnostic and interventional radiology, nuclear medicine, and radiation oncology). The learning outcomes of the training are presented as knowledge, skills and competences (KSC approach). Results: For the Basic section, KSCs were stratified in four subsections: (1) Medical imaging analysis and AI Basics; (2) Implementation of AI applications in clinical practice; (3) Big data and enterprise imaging, and (4) Quality, Regulatory and Ethical Issues of AI processes. For the Advanced section instead, a common block was proposed to be further elaborated by each subspecialty core curriculum. The learning outcomes were also translated into a syllabus of a more traditional format, including practical applications. Conclusions: This AI curriculum is the first attempt to create a guideline expanding the current educational framework for Medical Physicists in Europe. It should be considered as a document to top the sub-specialties' curriculums and adapted by national training and regulatory bodies. The proposed educational program can be implemented via the European School of Medical Physics Expert (ESMPE) course modules and – to some extent – also by the national competent EFOMP organizations, to reach widely the medical physicist community in Europe.